Grafias da vida entre o dano e a cura : o reconhecimento da violência e as potências do dizer-se nas mídias sociais - Patricia Prates Costa (2022)
Situated at the affective turn of communication, my dissertation2 seeks a sensitive writing through the threads and affective traits (in common or in estrangement) between narrative fragments written by women who, like me, experienced gender violence in close relationships. It is an autoethnographic inspired research from the subject that- with a search for a search for inspiration from my own women violence in search of an experience of violence in their own experiences of violence in their own social networks on the subject. This universe of approximation refers to support networks between women, to the management of female bodies and places of performativity. Considering as conceptual and methodological possibilities of work in the field of affections, testimonies and experience, this dissertation takes technologies of the self as political powers of transformation. In this way, I compose an affective journey that is guided to understand the ways of revealing, hiding and feeling in the experiences of violence suffered by women, paying attention to the constructions of being a woman and the ways of knowing violence embodied in our testimonies. It is important for this slide between the affective forces imbricated in this path, experimenting with languages, writings and possible modes of action to affect affections in audits and often without possible pronunciation.